Integridad: respuesta superadora a los dilemas éticos del hombre de empresa - Paladino, Marcelo (2005)
The various scandals that have shaken the corporate world have shown the need to analyze once again the ethic foundations of the corporation. It is not enough to issue a simple negative judgment; we must learn from failure and reflect on its causes. Why didn’t these companies fulfill theirmissions? What happened to their fundamental values? What happened to the personal convictionsof their general managers, with their vision of the future, with their contributions for the country and the community? Experience shows that it is not enough to merely propose worthy goals, guiding values or policies in favor of the environment and the community. It is necessary that all these propositions originate in the personal convictions of each individual, so that each actionwill have a distinctive, personal mark. Integrity must be found in the center of each individual and corporation. This paper presents integrity as a superior concept amongst the values and virtues which are normally mentioned; it implies that management must adopt the enabling attitudes andabilities they need to carry out their work properly.